Successful antibiotic stewardship in hospitalised children in a developing nation. (December 2020) - Mustafa, Fatima; Koekemoer, L.A.; Green, Robin J.; Turner, Astrid C.; Becker, Piet; van Biljon, Gertruida
Highlights: This is a report of a successful paediatric antimicrobial stewardship programme. The programme is operating in a central hospital in a developing country. Viral respiratory tract infections do not require antibiotics. Antibiotic stewardship programmes require continual re-evaluation. Abstract: Objectives: Increasing antimicrobial resistance has become a looming threat to paediatric health and, therefore, health facilities are obliged to practice antimicrobial stewardship. This study was undertaken to review stewardship adherence in the Department of Pediatrics at the Central Hospital, Pretoria, South Africa. Methods: Antibiotic prescriptions of children admitted to hospital were reviewed for consistency with the national essential medicines list from January 2017 to January 2019. Medical records of children were reviewed to obtain the primary diagnosis, requested laboratory investigations and antibiotic prescription practices. The management was adjudicated as consistent with policy by a score system. Results: This study reveals that management was in agreement with standard guidelines in 69.3% of cases, with a range of 33–77%. From the start of the study in January 2017 to the final date in January 2019 there was a significant increase in the number of patients with respiratory tract infections who were treated correctly, increasing from 41% to 73% at study end. Conclusions: This study is the first to report the success of antibiotic stewardship in children admitted to a tertiary hospital in South Africa. However, it is critical that antibiotic stewardship be continued and antibiotic prescriptions be aligned with guidelines.